The first Lithuanian mathematical terms - Pekarskas, Vidmantas; Pekarskienė, Aldona (Lietuvos matematikos rinkinys, 2004)
The origin of the first Lithuanian mathematical terms is analyzed in this article. The reasons of a choice of terms are considered. The first Lithuanian mathematical terms can be divided into three groups: international words; the words translated from Polish, German and Russian languages; the original terms which have been made up by the authors of the first Lithuanian textbooks on mathematics.
Keywords: mathematical terms